Bitext Generation Through Rich Markup. - Casillas, Arantza; Martínez, Raquel (Computers & the Humanities, 2004)
This paper reports on a method for exploiting a bitext as the primary linguistic information source for the design of a generation environment for specialized bilingual documentation. The paper discusses such issues as Text Encoding Initiative (TEI), proposals for specialized corpus tagging, text segmentation and alignment of translation units and their allocation into translation memories, Document Type Definition (DTD), abstraction from tagged texts, and DTD deployment for bilingual text generation. The parallel corpus used for experimentation has two main features: